Analysis of the Economic and Social Impact Study of the Application of Artificial Intelligence in the Agricultural Sector: A Multidisciplinary Study - Suharta, Suharta (HM Publisher, 2024)
Introduction: Agriculture is an important sector in the global and national economy. Artificial intelligence (AI) has great potential to increase the efficiency and productivity of the agricultural sector. This research aims to analyze the economic and social impacts of implementing AI in the agricultural sector. Methods: This research uses a multidisciplinary study method, combining qualitative and quantitative approaches. Data was collected through surveys, interviews, and secondary data analysis. Results: The application of AI in the agricultural sector can increase efficiency and productivity. AI can help farmers in various aspects, such as land processing, fertilization, pest control, and harvesting. The application of AI can create new jobs in the agricultural sector. However, the application of AI can also have several social impacts, such as unemployment and the digital divide. Conclusion: The application of AI in the agricultural sector has great potential to increase efficiency, productivity, and employment. However, it is important to consider the social impacts of implementing AI and formulate appropriate policies to address it.